ERS technical standard on bronchial challenge testing: general considerations and performance of methacholine challenge tests. Issue 5 (2nd May 2017) - Coates, Allan L.; Wanger, Jack; Cockcroft, Donald W.; Culver, Bruce H.; ,; Diamant, Zuzana; Gauvreau, Gail; Hall, Graham L.; Hallstrand, Teal S.; Horvath, Ildiko; de Jongh, Frans H.C.; Joos, Guy; et al.
This international task force report updates general considerations for bronchial challenge testing and the performance of the methacholine challenge test. There are notable changes from prior recommendations in order to accommodate newer delivery devices. Rather than basing the test result upon a methacholine concentration (provocative concentration (PC20 ) causing a 20% fall in forced expiratory volume in 1 s (FEV1 )), the new recommendations base the result upon the delivered dose of methacholine causing a 20% fall in FEV1 (provocative dose (PD20 )). This end-point allows comparable results from different devices or protocols, thus any suitable nebuliser or dosimeter may be used, so long as the delivery characteristics are known. Inhalation may be by tidal breathing using a breath-actuated or continuous nebuliser for 1 min (or more), or by a dosimeter with a suitable breath count. Tests requiring maximal inhalations to total lung capacity are not recommended because the bronchoprotective effect of a deep breath reduces the sensitivity of the test. The new ERS recommendation for methacholine challenge tests will be the provocative dose rather than concentration http://ow.ly/FBe5309yXn2